Tophaceous Gout with Atypical Localization without Hyperuricemia or an Inflammatory Gout Attack - Hacı Bayram TOSUN; Sancar SERBEST; Murat BALOĞLU; Mustafa Erkan İNANMAZ and Kamil Çağrı KÖSE (Archives of Rheumatology, 2013)
Tophaceous gout which typically develops following recurrent acute attacks, accounts for 10% of all gout cases. Although gout is known as a condition which primarily affects male gender, 5% of the patients are women with the majority being postmenopausal during the first attack. Tophaceous gout is frequently polyarticular in women. A solitary tophus which is seen as a soft tissue mass without inflammatory joint disease can be confused with neoplastic conditions. In this article, we report a 30-year-old female case of tophaceous gout with atypical localization presenting without hyperuricemia or an acute inflammatory gout attack.